Stretchable Film
A stretch film with an olefin elastomer and inorganic filler addresses breathability issues by achieving controlled porosity and stretchability, enhancing comfort and air permeability.
Patent Information
- Application Number
- JP2021003735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-13
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-01-13
AI Technical Summary
Existing stretchable films with olefin elastomers have poor breathability, leading to stuffiness and reduced comfort when worn, and the process of adding inorganic fillers to enhance air permeability does not effectively create pores due to resin-inorganic substance separation issues.
A stretch film composed of an olefin elastomer and inorganic filler with controlled composition and manufacturing processes to achieve both excellent stretchability and breathability, featuring an air permeability of 5000 s/100 ml or less and a permanent strain of 20% or less.
The film achieves both excellent stretchability and breathability, ensuring comfort and air permeability through controlled porosity and material separation during stretching.
Smart Images

Figure 0007613920000003 
Figure 0007613920000004 
Figure 0007613920000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a stretch film. [Background technology]
[0002] Stretch films are used in a wide range of fields, including hygiene products, sporting goods, and medical products, to improve handling, wearing comfort (fit), etc. For example, they are used in garments such as underwear, waistbands of disposable diapers, side panels, leg gathers, incontinence products, sanitary napkins, bandages, surgical drapes, tightening bands, hats, swimming trunks, sports supports, medical product supports, bandages, etc.
[0003] As this stretch film, for example, one that contains an olefin resin including an olefin elastomer and a filler, in which the content of the filler is 100 to 300 parts by weight per 100 parts by weight of the olefin resin, and has voids on the surface has been proposed. It is described that such a configuration can provide a stretch film with excellent stretchability and excellent breathability (for example, see Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-204634 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the stretch film described in Patent Document 1, the olefin-based elastomer has elasticity and poor breathability, so there was a problem that sanitary products, etc. became stuffy when worn, reducing the comfort of use.
[0006] This stretch film is obtained by preparing an unstretched film using a material to which an inorganic filler such as calcium carbonate has been added, and then stretching the unstretched film. Generally, when an inorganic substance is added to a resin and stretched, dissociation occurs between the resin and the inorganic substance, forming holes, and thus breathability can be imparted. However, when a similar process is performed on a stretchable material, the resin stretches and no dissociation occurs between the resin and the inorganic substance, so breathability is not achieved. As a result, it has been difficult to achieve both breathability and stretchability.
[0007] Therefore, the present invention has been made in consideration of the above problems, and an object of the present invention is to provide a stretch film that can achieve both excellent stretchability and breathability. [Means for solving the problem]
[0008] In order to achieve the above object, the stretch film of the present invention is a stretch film containing an olefin-based elastomer and an inorganic filler, and is characterized in that the air permeability measured by an Oken air permeability tester is 5000 s / 100 ml or less, and the permanent set in at least one direction described below is 20% or less.
[0009] (Permanent deformation of stretch film) A rectangular test piece measuring 100 mm in one direction of the film and 25 mm in the direction perpendicular to the one direction is cut from the stretch film, and this test piece is fixed to the grips of the testing machine so that the distance between the grips is 25 mm. The test piece is stretched in the longitudinal direction at a speed of 254 mm / min so that the elongation (elongation ratio) calculated by the following formula (1) is 100%, and then the test piece is immediately contracted at the same speed, and the permanent set [%] is calculated using the following formula (2).
[0010] Elongation [%] = (L1-L0) / L0 × 100 (1) Permanent set [%] = (L2-L0) / L0 x 100 (2)
[0011] where L0 is the distance between the grips (mm) before stretching, L1 is the distance between the grips (mm) after stretching, and L2 is the distance between the grips (mm) when the load on the test piece (N / 25 mm) becomes 0 when contracting. Effect of the Invention
[0012] According to the present invention, it is possible to provide a stretch film that can achieve both excellent stretchability and breathability, and a method for producing the same. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a plan view illustrating a stretch film according to a first embodiment of the present invention. [Diagram 2] FIG. 4 is a cross-sectional view illustrating a stretch film according to a second embodiment of the present invention. [Diagram 3] FIG. 4 is a plan view illustrating a stretch film according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The stretch film of the present invention will be specifically described below. Note that the present invention is not limited to the following embodiments, and can be appropriately modified and applied within the scope of the present invention.
[0015] (First embodiment) The stretch film of the present embodiment is a film-like molded article containing an olefin-based elastomer and an inorganic filler.
[0016] <Olefin elastomer> The olefin elastomer used in the present invention may be a copolymer or homopolymer mainly composed of an olefin having 3 or more carbon atoms, or a copolymer mainly composed of ethylene and an olefin having 3 or more carbon atoms.
[0017] More specifically, for example, (1) α-olefin homopolymers such as propylene homopolymers and 1-butene homopolymers having low stereoregularity, (2) α-olefin copolymers such as propylene-ethylene copolymers, propylene-ethylene-1-butene copolymers, 1-butene-ethylene copolymers, 1-butene-propylene copolymers, 4-methylpentene-1-propylene copolymers, 4-methylpentene-1-1-butene copolymers, 4-methylpentene-1-propylene-1-butene copolymers, propylene-1-butene copolymers, ethylene-propylene copolymers, ethylene-hexene copolymers, and ethylene-octene copolymers, (3) ethylene-α-olefin-diene terpolymers such as ethylene-propylene-ethylidenenorbornene copolymers, ethylene-propylene-butadiene copolymers, and ethylene-propylene-isoprene copolymers. Also, elastomers in which the above-mentioned elastomers are dispersed in a matrix of crystalline polyolefins may be used. The olefin-based elastomers may be used alone or in combination of two or more kinds.
[0018] Olefin elastomers are generally composed of hard segments that govern basic physical properties such as mechanical properties, and soft segments that govern elasticity, which is a rubber-like property. An olefin elastomer whose hard segment is made of polypropylene is called a propylene elastomer, and one whose hard segment is made of polyethylene is called an ethylene elastomer. Examples of the soft segment of an olefin elastomer include EPDM, EPM, EBM, IIR, hydrogenated styrene butadiene rubber (HSBR), NBR, and acrylic rubber (ACM). In the case of a propylene elastomer, the propylene unit content relative to all units is preferably 70% by mass to 95% by mass, and more preferably 80% by mass to 90% by mass. If the propylene unit content of the hard segment is 70% by mass or more, the strength is improved, and excellent moldability is obtained, and if it is 95% by mass or less, excellent elasticity is obtained due to the elasticity of the soft segment.
[0019] In order to obtain excellent stretchability, the content of the olefin-based elastomer in the entire stretch film is preferably 15% to 50% by mass, more preferably 20% to 40% by mass, based on 100% by mass of the stretch film. If the content of the propylene-based elastomer is within the above range, excellent stretchability can be obtained due to the elasticity of the soft segment contained in the elastomer.
[0020] <Inorganic fillers> The inorganic filler is a component for forming through holes by making the film porous. By carrying out a stretching process while containing this inorganic filler, the stretchable film of this embodiment can exhibit excellent breathability.
[0021] Examples of the inorganic filler include calcium carbonate, zeolite, silica, titanium oxide, calcium oxide, magnesium oxide, zinc oxide, clay, mica, barium sulfate, magnesium hydroxide, etc. The inorganic filler may be used alone or in combination of two or more kinds.
[0022] The inorganic filler content of the entire stretch film is preferably 50% by mass to 70% by mass, more preferably 60% by mass to 65% by mass, based on 100% by mass of the stretch film. If the inorganic filler content is within the above range, the stretching process promotes porosity.
[0023] The average particle size of the inorganic filler is preferably 0.8 to 15 μm. If the average particle size of the inorganic filler is 0.8 μm or more, secondary aggregation of the inorganic filler is suppressed and dispersibility in the resin is good, and if it is 15 μm or less, there is no hole due to drawdown during extrusion and excellent moldability is achieved.
[0024] The term "average particle size" used herein refers to the particle size of 50% of the particles in the particle size distribution measured by a particle size distribution meter.
[0025] <Other ingredients> The stretch film may contain components other than the above-mentioned olefin-based elastomer, provided that the elasticity of the stretch film is not impaired.
[0026] Examples of other components include olefin resins, amide antiblocking agents (such as stearic acid amide), plasticizers, UV absorbers, antioxidants, weather stabilizers, antistatic agents, colorants, antifogging agents, metal soaps, waxes, mildew inhibitors, antibacterial agents, nucleating agents, flame retardants, lubricants, etc. The other components may be made into a master batch and added to the material for the stretch film.
[0027] <Olefin resin> The olefin resin is preferably one that is compatible with the above-mentioned olefin elastomer, such as a polyethylene resin or a polypropylene resin. The olefin resin may be used alone or in combination of two or more kinds.
[0028] For example, the polyethylene resin may be low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), ultra-low-density polyethylene (ULDPE), or the like.
[0029] In addition, from the viewpoint of improving breathability by contributing to fixation of pores, the content of the olefin resin in the entire stretch film is preferably less than 10% by mass out of 100% by mass of the stretch film. This is because if it is 10% by mass or more, the stretchability of the film may be significantly deteriorated since ordinary polyethylene itself has no stretchability.
[0030] From the viewpoint of improving air permeability, it is preferable to use low-density polyethylene as the polyethylene resin, and the content of low-density polyethylene in the entire stretch film is less than 10% by mass.
[0031] <Through hole> Fig. 1 is a plan view showing a stretch film of the present embodiment. As shown in Fig. 1, a plurality of through holes 2 are formed in the stretch film 1 of the present invention. The through holes 2 are formed by performing a stretching process on the raw film before it is made porous, as described later.
[0032] Note that Figure 1 shows a stretch film when stretched in the mechanical axis (longitudinal) direction (hereinafter referred to as "MD") of the film, but when stretched in a direction perpendicular to the MD (hereinafter referred to as "TD"), a horizontally elongated through hole 2 is formed in the TD.
[0033] In the stretch film 1 of this embodiment, the raw film containing the inorganic filler 3 is stretched to make it porous.
[0034] The diameter of the through-holes 2 is preferably 1 μm to 100 μm. If the diameter is 1 μm or more, the holes will not be blocked even in a stretchable material such as an elastomer, and excellent breathability can be obtained, and if the diameter is 100 μm or less, waterproofness can be obtained.
[0035] The diameter of the through-holes 2 is the average value of the opening diameters of the through-holes 2 at 50 randomly selected locations.
[0036] <Method of manufacturing stretch film> Next, the method for producing the stretch film of this embodiment will be described in detail.
[0037] The stretch film of the present embodiment is produced by forming a raw material containing the above-mentioned olefin-based elastomer and inorganic filler into a film shape using an extruder.
[0038] More specifically, first, an olefin-based elastomer, an inorganic filler, and, if necessary, other components such as the above-mentioned olefin-based resin are mixed in a predetermined blending ratio, extruded into a strand shape using a corotating twin-screw extruder equipped with a strand die, and cut to obtain pellets.
[0039] Next, the pellets are melt-extruded in a single-screw extruder equipped with a T-die to form a film, and the film is taken up on a take-up roll to obtain a raw film before being made porous.
[0040] The raw film is then subjected to uniaxial stretching to make the raw film porous, producing a stretch film 1 having a plurality of through holes 2 as shown in Fig. 1. The stretching method is not particularly limited, and examples thereof include roll stretching, tenter stretching, and gear stretching.
[0041] The above-mentioned uniaxial stretching treatment refers to a stretching treatment carried out in either the MD or TD direction as shown in Fig. 1. Note that a biaxial stretching treatment in which stretching is carried out in both the MD and TD directions may also be carried out.
[0042] The stretching temperature in the uniaxial stretching process is 20° C. or higher and lower than 70° C. If the temperature is lower than 20° C., the through holes formed due to the elasticity of the olefin-based elastomer may be blocked, and sufficient moisture permeability may not be obtained. If the stretching temperature is higher than 70° C., the stretch film may melt and break.
[0043] The stretching ratio in the uniaxial stretching process is 1.8 to 6 times. If the stretching ratio is 1.8 or more, the stretching process promotes porosity, further improving the moisture permeability of the stretch film, but if the stretching ratio is more than 6, the film may break when stretched. The "stretching ratio" here refers to the multiple of the length of the film after stretching to the length of the film before stretching in the stretching direction.
[0044] Furthermore, the stretch film of this embodiment produced by the above-mentioned method has an air permeability of 5000s / 100ml or less as measured by an Oken air permeability tester, making it possible to obtain excellent breathability.
[0045] Furthermore, the stretch film of the present embodiment has a permanent set of 20% or less, making it possible to obtain excellent stretchability.
[0046] The term "permanent set" used herein refers to a value calculated by the following method.
[0047] A rectangular test piece of 100 mm in one direction of the film and 25 mm in the direction perpendicular to the one direction is cut from the stretch film, and the test piece is fixed to the gripper of a precision universal testing machine (Shimadzu Corporation, Autograph AG-5000A) so that the distance between the grippers is 25 mm. The test piece is then stretched in the longitudinal direction at a speed of 254 mm / min so that the elongation (elongation ratio) calculated by the following formula (1) is 100%, and then the test piece is immediately contracted at the same speed. The permanent set [%] is then calculated from the following formula (2).
[0048] Elongation [%] = (L1-L0) / L0 × 100 (1) Permanent set [%] = (L2-L0) / L0 x 100 (2)
[0049] where L0 is the distance between the grips (mm) before stretching, L1 is the distance between the grips (mm) after stretching, and L2 is the distance between the grips (mm) when the load on the test piece (N / 25 mm) becomes 0 when contracting.
[0050] The thickness of the raw film before stretching is preferably 10 to 80 μm, more preferably 20 to 60 μm. If the thickness of the raw film is 10 μm or more, the handling properties such as wrinkles during winding and trimming cutability during slitting can be ensured. If the thickness of the raw film is 80 μm or less, the stretch film after stretching can have sufficient breathability.
[0051] The thickness of the stretched film after stretching is 40-60% of the original film when stretched by heating, and 80-100% of the original film when stretched at room temperature. In the case of gear stretching, the unstretched part has the same thickness as the original film, and the stretched part is 80-100% of the original film.
[0052] By the above method, in this embodiment, a stretch film that has both excellent stretchability and breathability can be obtained.
[0053] The stretch film may be a single layer or may be a multi-layer film having two or more layers. When the stretch film is a multi-layer film, the composition and thickness of each layer may be the same or different. When the stretch film is a multi-layer film, the thickness refers to the total thickness of the multi-layer film.
[0054] Second embodiment Next, a second embodiment of the present invention will be described. Note that the same components as those in the first embodiment are given the same reference numerals and the description thereof will be omitted.
[0055] Fig. 2 is a cross-sectional view showing a stretch film according to a second embodiment of the present invention. As shown in Fig. 2, the stretch film 10 of this embodiment includes an elastomer layer 5 made of a stretch film containing an olefin-based elastomer and an inorganic filler as described in the first embodiment above, and surface layers 6 and 7 laminated on the surface of the elastomer layer 5.
[0056] The elastomer layer 5 may contain other components as explained in the first embodiment above, as long as the elasticity of the elastic film 10 is not impaired.
[0057] (Surface layer) The surface layers 6 and 7 are layers for suppressing the occurrence of blocking in the stretch film 10.
[0058] 2, the surface layers 6, 7 are provided on either or both of the first and second surfaces of the elastomer layer 5, but from the viewpoint of sufficiently suppressing the occurrence of blocking of the stretch film 10, it is preferable that the surface layers 6, 7 are provided on both the first and second surfaces of the elastomer layer 5. Note that the surface layers 6, 7 may be the same type of surface layer or different types of surface layers.
[0059] The surface layers 6, 7 contain an olefin resin (excluding olefin elastomers) and preferably further contain an inorganic filler. The surface layers 6, 7 may contain other components as necessary within the range that does not impair the effects of the present invention.
[0060] <Olefin resin> The olefin resin is preferably one that is compatible with the olefin elastomer in the elastomer layer 5, and is, for example, a polyethylene resin or a polypropylene resin. From the viewpoint of improving the stretchability of the surface layers 6, 7, polyethylene is preferred, and from the viewpoint of improving the breathability of the surface layers 6, 7, polypropylene resin is preferred.
[0061] For example, polyethylene resins include low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and high density polyethylene (HDPE).
[0062] Examples of polypropylene resins include homopolypropylene (H-PP) obtained by polymerizing propylene alone, random polypropylene (R-PP) obtained by copolymerizing ethylene and propylene, and block polypropylene (B-PP) obtained by polymerizing homopolypropylene and then copolymerizing ethylene and propylene in the presence of homopolypropylene. The olefin resins may be used alone or in combination of two or more kinds.
[0063] From the viewpoint of obtaining excellent elasticity, the content of the olefin resin in the entire surface layer is preferably 30% by mass to 60% by mass, more preferably 40% by mass to 50% by mass, of 100% by mass of the surface layer.
[0064] <Inorganic fillers> The inorganic filler is a component that imparts slipperiness to the surfaces of the surface layers 5 and 6, thereby further suppressing the occurrence of blocking in the stretch film 10. It is also a component that is used to form the through holes 2 by making the film porous, and by carrying out a stretching process in a state containing this inorganic filler, the stretch film of the present embodiment can exhibit excellent breathability.
[0065] Examples of the inorganic filler include calcium carbonate, zeolite, silica, titanium oxide, calcium oxide, magnesium oxide, zinc oxide, clay, mica, barium sulfate, magnesium hydroxide, etc. The inorganic filler may be used alone or in combination of two or more kinds.
[0066] The content of the inorganic filler in the entire surface layer is preferably 40% by mass or more and 70% by mass or less, and more preferably 50% by mass or more and 60% by mass or less, of 100% by mass of the surface layer. If the content of the inorganic filler is within the above range, the porosity is promoted by performing the stretching treatment.
[0067] The average particle size of the inorganic filler is preferably 0.8 to 10 μm. If the average particle size of the inorganic filler is 0.8 μm or more, secondary aggregation of the inorganic filler is suppressed and dispersibility in the resin is improved, and if it is 10 μm or less, the feel is improved.
[0068] <Other ingredients> Other components include amide-based antiblocking agents (such as stearic acid amide), plasticizers, UV absorbers, antioxidants, weather stabilizers, antistatic agents, colorants, antifogging agents, metal soaps, waxes, mildew inhibitors, antibacterial agents, nucleating agents, flame retardants, lubricants, etc. The other components may be made into masterbatches and added to the material for the stretch film.
[0069] <Through hole> Fig. 3 is a plan view showing a stretch film of this embodiment. As shown in Fig. 3, a plurality of through holes 2 are formed in the stretch film 10 of the present invention. The through holes 2 are formed by performing a stretching process on the original film before it is made porous, as described later. In the stretch film 10 of this embodiment, the original film is made porous by performing a stretching process in a state in which it contains the above-mentioned inorganic filler 3.
[0070] Although FIG. 3 shows a stretch film in which stretching processing is performed in MD, when stretching processing is performed in TD, horizontally elongated through holes 2 are formed in TD.
[0071] As described above, the porous structure can be promoted during the stretching process by including an inorganic filler in the surface layers 6 and 7. The diameter of the through holes 2 is preferably 1 μm to 100 μm, as in the first embodiment.
[0072] <Method of manufacturing stretch film> Next, the method for producing the stretch film of this embodiment will be described in detail.
[0073] In the stretch film of this embodiment, as in the case of the first embodiment described above, first, an olefin-based elastomer, an inorganic filler, and, if necessary, other components such as the above-mentioned olefin-based resin are mixed in a predetermined mixing ratio, extruded into a strand shape using a corotating twin-screw extruder equipped with a strand die, and cut to obtain pellets for forming the elastomer layer. Similarly, an olefin-based resin, and, if necessary, an inorganic filler, and other components are mixed in a predetermined mixing ratio, extruded into a strand shape using a corotating twin-screw extruder equipped with a strand die, and cut to obtain pellets for forming the surface layer.
[0074] Next, using an extruder equipped with a T-die, the pellets for forming the elastomer layer and the pellets for forming the surface layer are extruded at a predetermined temperature, and a cast film process is used to obtain an unporous raw film having an elastomer layer, a first surface layer provided on a first surface of the elastomer layer, and a second surface layer provided on a second surface of the elastomer layer.
[0075] The raw film is then subjected to uniaxial stretching at the same stretching temperature and stretch ratio as in the first embodiment described above, thereby making the raw film porous, and producing a stretch film 10 having a plurality of through holes 2 as shown in Fig. 3. The stretching method is not particularly limited, and examples thereof include roll stretching, tenter stretching, and gear stretching.
[0076] The above-mentioned uniaxial stretching treatment refers to a stretching treatment performed in either the MD or TD direction shown in Fig. 3. Note that a biaxial stretching treatment in which stretching treatment is performed in both the MD and TD directions may also be performed.
[0077] Furthermore, in the stretch film of this embodiment produced by the above-mentioned method, as in the case of the first embodiment described above, the air permeability measured using an Oken air permeability tester is 5000 s / 100 ml or less, and the permanent set is 20% or less, making it possible to obtain a stretch film that has both excellent stretchability and breathability.
[0078] The thickness of the raw film before stretching is preferably 10 to 80 μm, more preferably 20 to 60 μm. If the thickness of the raw film is 10 μm or more, the handling properties such as wrinkles during winding and trimming cutability during slitting can be ensured. Furthermore, if the thickness of the raw film is 80 μm or less, sufficient breathability can be obtained.
[0079] The thickness of the elastomer layer 5 in the raw film is preferably 10 to 70 μm, and more preferably 20 to 50 μm. If the thickness of the elastomer layer 5 is 10 μm or more, sufficient stretchability can be obtained in the stretch film 10 after the stretching treatment. If the thickness of the elastomer layer 5 is 70 μm or less, sufficient breathability can be obtained in the stretch film 10 after the stretching treatment.
[0080] Furthermore, the thickness of the surface layers 6, 7 in the original film is preferably 1 to 6 μm, and more preferably 2 to 4 μm. If the thickness of the surface layers 6, 7 is 1 μm or more, the occurrence of blocking in the stretch film 10 after stretching can be sufficiently suppressed, and the breathability of the stretch film 10 can be improved. If the thickness of the surface layers 6, 7 is 6 μm or less, the stretchability of the stretch film 10 can be sufficiently obtained. Note that the surface layers 6, 7 may be the same thickness or different thicknesses.
[0081] The thickness of the stretchable film 10 after stretching is 40-60% of the original film when stretched at room temperature, and 80-100% of the original film when stretched at room temperature. In the case of gear stretching, the unstretched portion has the same thickness as the original film, and the stretched portion has a thickness of 80-100% of the original film.
[0082] Furthermore, from the viewpoint of improving elasticity, even in the case of a stretch film 10 in which the thickness ratio of the surface layers 6, 7 to the entire stretch film is small, it is preferable that the thickness ratio of the surface layer 6 (or surface layer 7) to the elastomer layer 5 of the original film and stretch film 10 is surface layer:elastomer layer = 1:10 to 1:35.
[0083] The stretch film may be a single layer or may be a multi-layer film having two or more layers. When the stretch film is a multi-layer film, the composition and thickness of each layer may be the same or different. When the stretch film is a multi-layer film, the thickness refers to the total thickness of the multi-layer film. EXAMPLES
[0084] The present invention will be described below based on examples. Note that the present invention is not limited to these examples, and these examples can be modified or changed based on the spirit of the present invention, and they are not excluded from the scope of the present invention.
[0085] The materials used to prepare the stretch film are listed below. (1) Inorganic filler: calcium carbonate (manufactured by Shiraishi Calcium Co., Ltd., product name: PO-150B-10) (2) LLDPE: Linear low-density polyethylene, density: 0.92 g / cm 3 , MFR: 2.3g / 10min (Dow Chemical, product name: Dowlex 2047G) (3) HDPE: High density polyethylene, density: 0.951g / cm 3 , MFR: 9.1g / 10min (Asahi Kasei Corporation, product name: Hizex2110JH) (4) R-PP: Random polypropylene, density: 0.90 g / cm 3 , MFR: 6.7g / 10min (Prime Polymer Co., Ltd., product name: F227) (5) Propylene-based elastomer (Vistamaxx (registered trademark) 6102FL (manufactured by ExxonMobil, propylene-ethylene copolymer, ethylene unit content: 16% by mass) (6) LDPE: Low density polyethylene, density: 0.922g / cm 3 , MFR: 0.3g / 10min (manufactured by Sumitomo Chemical Co., Ltd., product name: Sumikasen, F101-1)
[0086] Example 1 <Preparation of stretchable film> First, the materials shown in Table 1 were mixed to prepare a material of Example 1 having the composition (parts by mass) shown in Table 1. Next, this material was extruded in the form of strands at 200°C using a co-rotating twin-screw extruder (manufactured by JSW Corp., product name: TEX28V-42CW-4V) equipped with a strand die, and cut to obtain pellets.
[0087] Next, the pellets were formed into a film by melt extrusion (extrusion temperature: 200°C) using a single-screw extruder (manufactured by Nagata Seisakusho) equipped with a T-die, and the film was wound up on a take-up roll to obtain the original film before being made porous.
[0088] Then, this raw film was subjected to uniaxial stretching in the MD under the conditions of the stretching temperature and stretch ratio shown in Table 1, thereby making the raw film porous and producing an elastic film with multiple through holes.
[0089] <Air permeability measurement> Next, the air permeability of the prepared stretched film was measured using an Oken type air permeability meter (sec / 100cc) (manufactured by Asahi Seiko Co., Ltd., product name: EG01-6-1MR). In this measurement, those that did not show air permeability were expressed as 99999 (sec / 100cc). The results are shown in Table 1.
[0090] <Measurement of permanent deformation> From the prepared stretch film, a rectangular test piece of 100 mm in one direction of the film and 25 mm in the direction perpendicular to the one direction was cut, and this test piece was fixed to the gripper of a precision universal testing machine (Shimadzu Corporation, Autograph AG-5000A) so that the distance between the grippers was 25 mm. Then, the test piece was stretched in the longitudinal direction at a speed of 254 mm / min so that the elongation (elongation ratio) calculated by the above formula (1) was 100%, and then the test piece was immediately contracted at the same speed. Then, the permanent set [%] in MD and TD was calculated from the above formula (2). The test was performed at room temperature (23°C ± 2°C). The above results are shown in Table 1.
[0091] (Examples 2 to 4) Except for changing the composition (parts by mass) of the stretch film and the conditions of the uniaxial stretching process to those shown in Table 1, a raw film having the thickness shown in Table 1 was stretched to produce a stretch film in the same manner as in Example 1 described above.
[0092] Then, the air permeability and the permanent deformation were measured in the same manner as in Example 1. The results are shown in Table 1.
[0093] Example 5 <Preparation of stretchable film> First, the materials shown in Table 1 were mixed to prepare materials for forming an elastomer layer and a surface layer of Example 5 having the compositions (parts by mass) shown in Table 1. Next, these materials were extruded in a strand shape using a co-rotating twin-screw extruder (manufactured by JSW Corp., product name: TEX28V-42CW-4V) equipped with a strand die under a condition of 200°C, and cut to obtain pellets for forming an elastomer layer and pellets for forming a surface layer.
[0094] Next, using an extruder equipped with a T-die (manufactured by Sumitomo Heavy Industries Modern Co., Ltd.), the pellets for forming the elastomer layer and the pellets for forming the surface layer were extruded at 200°C, and a film having an elastomer layer, a first surface layer provided on a first surface of the elastomer layer, and a second surface layer provided on a second surface of the elastomer layer was formed by a cast film process method, and the film was taken up on a take-up roll to obtain a raw film before being made porous.
[0095] Then, this raw film was subjected to uniaxial stretching in the MD under the conditions of the stretching temperature and stretch ratio shown in Table 1, thereby making the raw film porous and producing an elastic film with multiple through holes.
[0096] Then, the air permeability and the permanent set were measured in the same manner as in Example 1. The results are shown in Table 1.
[0097] (Examples 6 to 16) Except for changing the composition of the surface layer (parts by mass), the composition of the elastomer layer (parts by mass), the thickness ratio between the surface layer and the elastomer layer, and the conditions of the uniaxial stretching process to those shown in Table 1, a raw film having the thickness shown in Table 1 was stretched to produce a stretch film in the same manner as in Example 5 described above.
[0098] Then, the air permeability and the permanent deformation were measured in the same manner as in Example 1. The results are shown in Table 1.
[0099] (Comparative Examples 1 to 9) Except for changing the composition of the surface layer (parts by mass), the composition of the elastomer layer (parts by mass), the thickness ratio between the surface layer and the elastomer layer, and the conditions of the uniaxial stretching process to those shown in Table 2, a raw film having the thickness shown in Table 2 was stretched to produce a stretch film in the same manner as in Example 5 described above.
[0100] Then, the air permeability and the permanent deformation were measured in the same manner as in Example 1. The results are shown in Table 2.
[0101] In addition, in Comparative Example 8, the thickness ratio between the surface layer and the elastomer layer of the original film was surface layer:elastomer layer=1:38, so when producing the original film, there were parts where the surface layer did not wrap around the elastomer layer, and a stretchable film could not be obtained.
[0102] In Comparative Example 9, the amount of inorganic filler blended in the elastomer layer was large, so that pellets for forming the elastomer layer could not be prepared.
[0103] Therefore, in Comparative Examples 8 and 9, it was not possible to measure the air permeability and the permanent deformation.
[0104] [Table 1]
[0105] [Table 2]
[0106] As shown in Table 1, the stretch films of Examples 1 to 16 have an air permeability of 5000 s / 100 ml or less as measured using an Oken air permeability tester, and a permanent set in at least one of the MD and TD directions of 20% or less, which indicates that excellent stretchability and breathability can be achieved at the same time.
[0107] On the other hand, as shown in Table 2, in the stretch film of Comparative Example 1, the thickness ratio between the surface layer and the elastomer layer of the original film was surface layer:elastomer layer=1:8, so that the proportion of the surface layer was large and the proportion of the resin component with low elastomeric properties was large, resulting in poor stretchability (permanent strain was greater than 20%).
[0108] In addition, in the stretch film of Comparative Example 2, the stretch temperature during film formation in the uniaxial stretching process was 70° C. or higher, so the stretch film melted and broke.
[0109] In the stretch film of Comparative Example 3, the thickness ratio of the surface layer to the elastomer layer of the original film is 1:8, so the proportion of the surface layer is large, and the proportion of the resin component with low elastomer properties is large, resulting in poor stretchability (permanent set is greater than 20%). Also, because the stretch ratio is low, pores are not sufficiently opened, resulting in poor breathability (air permeability is greater than 5000s / 100ml).
[0110] In addition, in the stretch film of Comparative Example 4, the stretch ratio during film formation in the uniaxial stretching process was less than 1.8 times, so the porosity caused by the uniaxial stretching process was not promoted, and the film had poor breathability (air permeability was greater than 5000 s / 100 ml).
[0111] In addition, in the stretch film of Comparative Example 5, the thickness ratio between the surface layer of the original film and the elastomer layer was surface layer:elastomer layer=1:8, and since LDPE was not blended into the elastomer layer, separation between the resin and the inorganic filler was unlikely to occur, and the film had poor breathability (air permeability was greater than 5000s / 100ml).
[0112] Furthermore, in the stretch film of Comparative Example 6, since LDPE is not blended into the elastomer layer, separation between the resin and the inorganic filler is unlikely to occur, and it is found that the film exhibits no breathability at all (air permeability is displayed as 99999s / 100ml).
[0113] Furthermore, in the stretch film of Comparative Example 7, since LDPE is not blended into the elastomer layer, separation between the resin and the inorganic filler is less likely to occur, and the film has poor breathability (air permeability is greater than 5000s / 100ml). [Industrial Applicability]
[0114] As described above, the present invention is suitable for stretch films and manufacturing methods thereof that are used, for example, in garments such as underwear, waistbands of disposable diapers, side panels, leg gathers, incontinence products, sanitary napkins, bandages, surgical drapes, tightening bands, hats, swimming trunks, sports supports, medical supporters, bandages, etc. [Explanation of symbols]
[0115] 1 Stretch film 2 Through holes 3. Inorganic fillers 5 Elastomer Layer 6,7 Surface layer 10 Stretch Film
Claims
1. A stretch film containing an olefin-based elastomer and an inorganic filler, The content of the olefin-based elastomer in the entire stretch film is 15% by mass or more and 50% by mass or less, out of 100% by mass of the stretch film; The content of the inorganic filler in the entire stretch film is 50% by mass or more and 70% by mass or less, out of 100% by mass of the stretch film; The stretch film contains low-density polyethylene, and the content of the low-density polyethylene in the entire stretch film is less than 10% by mass of 100% by mass of the stretch film; The air permeability measured by an Oken air permeability tester is 5000 s / 100 ml or less, A stretch film characterized in that the permanent deformation in at least one direction is 20% or less. (Permanent Deformation of Stretch Film) A rectangular test piece measuring 100 mm in one direction of the film and 25 mm in the direction perpendicular to the one direction was cut from the stretch film, and this test piece was fixed to the grips of a testing machine so that the distance between the grips was 25 mm. The test piece was stretched in the longitudinal direction at a speed of 254 mm / min so that the elongation (elongation ratio) calculated by the following formula (1) was 100%, and then the test piece was immediately contracted at the same speed, and the permanent set [%] was calculated using the following formula (2). Elongation [%] = (L1 - L0) / L0 × 100 (1) Permanent set [%] = (L2 - L0) / L0 x 100 (2) Here, L0 is the distance between the grips (mm) before stretching, L1 is the distance between the grips (mm) after stretching, and L2 is the distance between the grips (mm) when the load on the test piece (N / 25 mm) becomes 0 when contracting.
2. The present invention comprises an elastomer layer containing an olefin-based elastomer and an inorganic filler, and a surface layer laminated on at least one surface of the elastomer layer, a content of the olefin-based elastomer in the entire elastomer layer is 15% by mass or more and 50% by mass or less, based on 100% by mass of the elastomer layer; a content of the inorganic filler in the entire elastomer layer is 50% by mass or more and 70% by mass or less, based on 100% by mass of the elastomer layer; the elastomer layer contains low-density polyethylene, and a content of the low-density polyethylene in the entire elastomer layer is less than 10% by mass of 100% by mass of the elastomer layer; The air permeability measured by an Oken air permeability tester is 5000 s / 100 ml or less, A stretch film characterized in that the permanent deformation in at least one direction is 20% or less. (Permanent Deformation of Stretch Film) A rectangular test piece measuring 100 mm in one direction of the film and 25 mm in the direction perpendicular to the one direction was cut from the stretch film, and this test piece was fixed to the grips of a testing machine so that the distance between the grips was 25 mm. The test piece was stretched in the longitudinal direction at a speed of 254 mm / min so that the elongation (elongation ratio) calculated by the following formula (3) was 100%, and then the test piece was immediately contracted at the same speed, and the permanent set [%] was calculated using the following formula (4). Elongation [%] = (L1 - L0) / L0 × 100 (3) Permanent set [%] = (L2 - L0) / L0 x 100 (4) where L0 is the distance (mm) between the grips before stretching, L1 is the distance (mm) between the grips after stretching, and L2 is the distance (mm) between the grips when the load (N / 25 mm) of the test piece becomes 0 when contracting.
3. The stretch film according to claim 2, characterized in that the thickness ratio of the surface layer to the elastomer layer is surface layer:elastomer layer=1:10 to 1:
35.
4. The stretch film according to any one of claims 1 to 3, characterized in that it is stretched in at least one direction.
5. The stretch film according to any one of claims 1 to 4, characterized in that the olefin-based elastomer is a propylene-based elastomer.
6. The stretch film according to any one of claims 1 to 5, characterized in that a plurality of through holes are formed.
Citation Information
Patent Citations
Stretchable film and product including same
JP2016204634A
Breathable film
JP2017031292A
Porous stretchable film and method for producing the same, and composite sheet
JP2017164996A
Porous sheet
US4613643A
Stretchable film
WO2016013577A1